Data for: The Impact of Conspiracy Theories and Vaccine Knowledge on Vaccination Intention: A longitudinal study - Viscardi, Lucas (2024)
Supplementary material of The Impact of Conspiracy Theories and Vaccine Knowledge on Vaccination Intention: A longitudinal study